CITRA (IMAGE) PARIWISATA BALI DI ERA GLOBALISASI - Wisnu Bawa Tarunajaya (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2010)
Every tourism destination intends to strengthen its positive image to international tourists by slogan or icon which can directly represent or be associated with the destination. The image of tourism destination can be influenced by some variables such as organic image and modified-induce image. Data were collected using a set of questionnaire and then analyzed using SPSS program. The study found out that there are six factors of tourist perceptions image of Bali as a tourism destination namely: the infrastntcture of Bali is good, there are many tourist . activities offered, interesting culture and history, as a place for relaxed, safe, unique local way of life.